Exploring Biomimicry in the Students’ Design Process - Boga-Akyol, Miray; Timur-Ogut, Sebnem (Design and Technology Education: An International Journal, 2016)
Since the very early days of history, human beings ‘designed’ things by looking at nature. In our days, the use of nature in design has become more systematic and detailed. Although as old as humanity itself, use of nature especially in the field of design still offers novelty and often brings success in solving problems in a sustainable way. When it comes to industrial design education specifically, it seems to be a promising method to mimic the nature in designing new products; however different dynamics effect and sometimes prevent students to use natural analogy in their projects. It is observed that industrial design students aren’t eager to use biomimicry which is a type of natural analogy in their design projects although they learn about it in different courses as a creativity method. The study therefore aimed to find out about two issues related to the matter: a) trying to find out and understand the reasons behind this reluctance against the use of nature, b) if they were presented a methodology, in what ways this reluctance would be overcome and they would go beyond taking nature as not only a formal source of inspiration.